TRENDS IN CONTEMPORARY PARLIAMENTARY DEVELOPMENT AND INNOVATIVE EXAMPLES OF BEST PRACTICES OF THE NATIONAL ASSEMBLY OF THE REPUBLIC OF SERBIA - Vukadinović, Slobodan (Serbian political thought, 2024)
This paper aims to explore trends in contemporary parliamentary development and to determine the position of the Serbian National Assembly and domestic parliamentary practice about global processes. The theoretical legal analysis begins by examining the role of parliament in a modern democracy, expanding the understanding of parliamentary autonomy on multiple levels, the standards of a modern democratic parliament in the 21st century, and the growing significance of parliamentary diplomacy. Subsequently, through the application of comparative legal, legal historical, and legal dogmatic methods, it was established that the National Assembly of the Republic of Serbia has been recognized and highlighted as an example of excellent and innovative practice in the five-year global parliamentary studies published so far (especially in 2017 and 2022). In this context, the innovations introduced and institutionalized in the parliamentary practice and normative framework of the National Assembly of the Republic of Serbia over the past 15 years are discussed and identified. The focus is on the formation of informal parliamentary groups (GOPAC, Women’s Parliamentary Network, Green Parliamentary Group, Economic Caucus, Energy Forum, Focus Group for the Implementation of Sustainable Development Goals), the introduction and regular holding of public hearings, and committee sessions outside the seat of the National Assembly, the green chair mechanism, the budget office, the public finance oversight portal, etc. Finally, the paper explores current topics that are at the forefront of global parliamentary development trends in the past year, as well as the most recently published results, particularly those related to the role of parliament in combating climate change and the indicators of a democratic parliament published at the end of 2023.